(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of present study was to investigate level of interdependence between prevalence of Ghutti and education of newborn’s mothers. Study Design: Cross-sectional Place and Duration of the Study: This study was carried out at Village Khewayaali, Tehsil Wazirabad, District Gujranwala from Aug-2013 to Oct-2013. Materials and Methods: Data was collected while administrating a fully structured questionnaire. Tool was implemented with the help of women enumerator after improving the areas highlighted during the pre testing. A sample of 324 lactating women was randomly selected out of total population of lactating mothers. SPSS was used for data analysis. Results: As 95 % of lactating women respondent of this research confirmed that they had given their child Ghutti prior to the breastfeed. But on the other side, 80% of the total respondents also confirmed that they had fed their child in first 04 hours after birth and did not waste the highly nutritive Colostrum. Whereas, comparison of mothers’ education with the use of Ghutti delineated that the practice is equally common among illiterate and educated mothers both. Illiterate mothers were 21% of the total respondents and use of Ghutti was equally present in rest 79% educated mothers as well thus the practice was found among 100% respondents. Conclusion: Current study explored that education has no influence over this deeply rooted a cultural practices and norms. As mothers despite being educated and much aware with the benefits of breastfeed performed this tradition under the persuasions of adult relatives especially mother in law.